1993
DOI: 10.1016/0014-5793(93)80059-4
|View full text |Cite
|
Sign up to set email alerts
|

Ankyrin‐like proteins of variola and vaccinia viruses

Abstract: Computer analysis of full coding sequences of variola major virus strain India‐1967 genome and vaccinia virus strain Copenhagen genome have been carried out. A wide set of proteins containing ankyrin‐like repeats have been identified for both viruses. Only three proteins of this family of the studied viruses are highly homologous. The rest of the proteins are different. The possible role of such proteins in determination of virus tissue tropism is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…These deletions occur in a region that, in VACV-COP, codes for several genes related to immune evasion, especially ORFs C21L to C17L that are the same as B23R to B27R and B16R . The proteins produced from ORFs C21L to C17L (in the left ITR) and B23R to B27R (in the right ITR) belong to the family of ankyrin-containing motif proteins, which includes eukaryotic proteins that regulate the complement system [53]. These proteins in OPXV also inhibit the alternative and classical pathways of complement activation, and contribute to virulence in the rabbit model of infection [2].…”
Section: Resultsmentioning
confidence: 99%
“…These deletions occur in a region that, in VACV-COP, codes for several genes related to immune evasion, especially ORFs C21L to C17L that are the same as B23R to B27R and B16R . The proteins produced from ORFs C21L to C17L (in the left ITR) and B23R to B27R (in the right ITR) belong to the family of ankyrin-containing motif proteins, which includes eukaryotic proteins that regulate the complement system [53]. These proteins in OPXV also inhibit the alternative and classical pathways of complement activation, and contribute to virulence in the rabbit model of infection [2].…”
Section: Resultsmentioning
confidence: 99%
“…The M150R product contains up to nine potential ANK repeats, although previous reports had predicted only five of them (4). M150R has homologs in orthopoxviruses, such as vaccinia, cowpox, and variola viruses (25,26). For these viruses, as well as for MV, predictions suggested that the protein is cytoplasmic.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitory roles in ubiquitination pathways are also possible (Mercer et al, 2005;Sonnberg et al, 2008;Zhang et al, 2009). Other poxvirus ANK/F-box proteins have been shown to inhibit virus-induced apoptosis (Ink et al, 1995;Mossman et al, 1996) and to influence virus virulence (Mossman et al, 1996;Wang et al, 2006), hostrange and tissue tropism (Shchelkunov et al, 1993;Ink et al, 1995;Johnston et al, 2005). Whether the PPV ANK/Fbox proteins have any of these functions is yet to be determined.…”
Section: Hautaniemi and Othersmentioning
confidence: 99%